10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
Global health has traditionally functioned as a project of high-income countries (HICs) addressing health challenges in low- and middle-income countries (LMICs). This "outward facing" orientation has created conceptual and operational boundaries that obscure the persistence of health inequities within HICs and perpetuates the false assumption that resource-rich nations have resolved fundamental health equity challenges in their own countries. In this essay we argue that HICs have global health problems of their own and should be considered legitimate sites for global health intervention. We propose an approach to doing global health in the global north that is based on reciprocal learning and where solutions to global health problems can also be found outside the borders of HICs. Complementing the extant scholarship on the need to decolonize global health, this essay highlights LMIC-led successes that can inform global health practice in the U.S. and Canada thus positioning global health as a truly egalitarian project.